Lipopolysaccharide from the Cyanobacterium Geitlerinema sp. Induces Neutrophil Infiltration and Lung Inflammation - Julie A. Swartzendruber; Rosalinda Monroy Del Toro; Ryan Incrocci; Nessa Seangmany; Joshua R. Gurr; Alejandro M. S. Mayer; Philip G. Williams; Michelle Swanson-Mungerson (Toxins, 2022)
Glucocorticoid-resistant asthma, which predominates with neutrophils instead of eosinophils, is an increasing health concern. One potential source for the induction of neutrophil-predominant asthma is aerosolized lipopolysaccharide (LPS). Cyanobacteria have recently caused significant tidal blooms, and aerosolized cyanobacterial LPS has been detected near the cyanobacterial overgrowth. We hypothesized that cyanobacterial LPS contributes to lung inflammation by increasing factors that promote lung inflammation and neutrophil recruitment. To test this hypothesis, c57Bl/6 mice were exposed intranasally to LPS from the cyanobacterium member, Geitlerinema sp., in vivo to assess neutrophil infiltration and the production of pro-inflammatory cytokines and chemokines from the bronchoalveolar fluid by ELISA. Additionally, we exposed the airway epithelial cell line, A549, to Geitlerinema sp. LPS in vitro to confirm that airway epithelial cells were stimulated by this LPS to increase cytokine production and the expression of the adhesion molecule, ICAM-1. Our data demonstrate that Geitlerinema sp. LPS induces lung neutrophil infiltration, the production of pro-inflammatory cytokines such as Interleukin (IL)-6, Tumor necrosis factor-alpha, and Interferongamma as well as the chemokines IL-8 and RANTES. Additionally, we demonstrate that Geitlerinema sp. LPS directly activates airway epithelial cells to produce pro-inflammatory cytokines and the adhesion molecule, Intercellular Adhesion Molecule-1 (ICAM-1), in vitro using the airway epithelial cell line, A549. Based on our findings that use Geitlerinema sp. LPS as a model system, the data indicate that cyanobacteria LPS may contribute to the development of glucocorticoid-resistant asthma seen near water sources that contain high levels of cyanobacteria.